Relationship Between Percutaneous Dilatational Tracheostomy Installation And Ventilator Weaning Process - Sartika Rajagukguk; Sabtria Winda Sari; Yulianti (Program Studi Keperawatan Universitas Muhammadiyah Tasikmalaya, 2023)
Percutaneous dilatational tracheostomy (PDT) is a tracheostomy technique by making a minimal incision to insert a guide wire in bedridden patients. Weaning is a series of processes of releasing mechanical ventilation assistance from the patient's body and takes place gradually, the culminating point of which is the process of extubation / release of artificial airways. The purpose of this study was to determine the relationship between the installation of a percutaneous dilatational tracheostomy and the process of weaning a ventilator in the ICU room of Awal Bros Hospital, Pekanbaru. This study used an analytic observational method using a cross sectional design with a total sample of 25 people using a total sampling technique. The results of this study used the chi square test and obtained a p value of 0.001 where the value is less than 0.05 (0.01 <0.05), so that means there is a relationship between Percutaneous Dilatational Tracheostomy (PDT) placement and the Weaning process, PDT is faster in the weaning process. This research is expected to be useful for patients who have Percutaneous dilatational tracheostomy installed so that they can quickly complete the ventilator weaning process.